ANALYSIS OF LEVELS IN SCOUTING IN REALIZING A SENSE OF NATIONALISM - Khafifah Rahmawani Siregar; Setiyani Br Saragih; Padilah Hoiriah Harahap (Journal of Quality Islamic Education Research, 2024)
The type of research used in this research is qualitative research. The data collection techniques used in this research are as follows: (1) Observation (Observation, documentation and traiangulation. The results of the research. Nationalism at the scout level is a manifestation of national awareness or national spirit. How does nationalism develop? application of a national way of thinking. National thinking can also be antithetical to regional or group ways of thinking. New behavior occurs when there is something that is needed to cause a reaction, namely stimulation, then the stimulus will cause a reaction or behavior. A form of human behavior that is invisible or hidden ( convert behavior) and visible behavior (overt behavior). nationalism at the scout level or nationalism within each paramuka member.